A STUDY OF THE FACTORS LEADING TO THE DEVELOPMENT OF CUSTOMER SATISFACTION: A CASE STUDY OF A PRIVATE BANKING INSTITUTION IN MANDALAY, MYANMAR - Kyawt Shinn Thant Zin; Komm Pechinthorn; Marlon Rael Astillero; Kitisak Tavisak; Tony Somathih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Recently, the market of the banking industries is growing rapidly in Myanmar. Therefore, banks not only need to focus on attracting new customers but also on maintaining the existing customers by providing the exceptional quality of services in order to survive in extremely stiff competitive industry. This research is attempted to investigate the 5 determinants which lead to customer satisfaction to Ayeyarwaddy Bank (AYA) in Mandalay, Myanmar. The questionnaires were distributed to 200 people who have been experienced of using the service of the 2 branches of the AYA Bank in the same city. Single & multiple linear regression model were used in order to test the hypotheses to find out the beta coefficient and significant level. The finding is that all of the service quality dimensions such as reliability, responsiveness, assurance, empathy and tangibility are rejected and statistically influenced on the customer satisfaction. Keywords: service quality, customer satisfaction, commercial bank